Associations between knowledge, attitudes, junk food consumption, and obesity risk among productive age adults in Aceh, Indonesia - Marniati Marniati; Chairanisa Anwar; Putri Mauliza (AcTion: Aceh Nutrition Journal, 2025)
Obesity has become a global public health problem with increasing prevalence. In Indonesia, Aceh ranks 10th out of 38 provinces, with an obesity prevalence of 24.4%. The number of obesity cases in Aceh Besar Regency among individuals of productive age has increased, despite an overall decline in patient visits between 2022 and 2024. This study aimed to analyze the relationship between knowledge, attitudes, and consumption habits of junk food and the risk of obesity in individuals of productive age. This observational analytical study with a case-control design was conducted in Aceh Besar between May and June 2025. The sample consisted of 120 productive-age adults (15–64 years) selected through proportional sampling methods. Knowledge, attitudes, and junk food consumption were measured using a structured questionnaire that had been tested for validity, and data analysis was performed using the chi-square test. The results showed a significant relationship between knowledge (p=0.017; OR=0.375) and junk food consumption habits (p=0.001; OR=0.269) and the incidence of obesity. Conversely, attitudes did not show a statistically significant relationship with the risk of obesity (p=0.083; OR=0.509). In conclusion, nutritional knowledge and junk food consumption habits are important factors in the risk of obesity in individuals of productive ages. Strengthening nutrition education and reducing fast-food consumption are recommended community-based obesity prevention measures.